Translanguaging as a pedagogical tool in the MTB-MLE classroom a framework for multilingual teachers in the Philippines - Suarez, Cecilia A. (College of Education, University of the Philippines Diliman, 2021)
This study was prompted by the results of an earlier study I conducted on "Translanguaging in the Bi/Multilingual Mother Tongue Classroom: A Case in the Philippines Context" which purported that translanguaging or shuttling between languages is a common linguistic behavior among teachers in the MTB-MLE classrooms. In particular, it is the observation that teachers engage in translanguaging indiscriminately which led me to further investigate the translanguaging techniques teacher use and their functions. Hence, this study aimed to answer the following research questions: 1.) What translanguaging techniques do teachers use? ; 2.) What functions do these translanguaging techniques fulfill?; and 3.) In what ways do teachers' translanguaging influence learners' engagement and concept understanding?. I used three primary tools to collect the data for this study, namely: Classroom Observation Form, Modified Stimulated Recall Questionnaire, and Semi-Structured Interview Protocol. Specifically, the Stimulated Recall method was modified for the purpose of this study since, unlike the typical method, I did not rely on the video recordings of classroom observations as stimuli to assist teacher respondents to recall specific instances of translanguaging. Instead, I used audio recordings, which I transcribed based on the actual instances of translanguaging which were selected through Moment Analysis. For the case study component of this research, I selected one of the five teacher-participants as the unit of analysis. In terms of data analysis, I used Moment Analysis and Discourse Analysis to identify the translanguaging techniques teacher use, their functions and their influence on learners' engagement and concept understanding. In addition, I also employed Descriptive Statistics to show quantitatively the influence of teachers' translanguaging on concept understanding. As answer to RQI, threee main translanguaging techniques were identified, namely: konwledge (re)construction, literal translation, and behavior (re)formation. Each of these technique has the following sub-categories: Knowledge (Re)construction through schema activation, a question, and repetition; Literal Translation of a source text or discussion, a concept, and lexicon or sentence; and Behavior (Re)formation through prompt clarification, verbal affirmation, and action or response correction. Thus, there were a total of nine translanguaging techniques that were observed teachers in this study used. As answer to RQ2, the functions of the identified translanguaging techniques include two primary purposes, which are to engage learners and to ensure concept understanding. In order to achieve this, the identified techniques serve the following specific functions: 1.) to activate schema; 2) to clarify; 3) to emphasize; 4) to scaffold; 5) to familiarize, 6) to affirm a learner's response; and/or 7) correct a learner's response or behavior. In terms of the results of the Case Study, the teacher's use of translanguaging promoted the following: 1) to promote learners' linguistic development; 2) to develop learners' metalinguistic awareness; 3) to develop a stronger sense of multilingual identity among the learners; and 4) to promote local cultural identity among the learners. As answer to RQ3, I found out through classroom observations and the teachers' responses in the Modified Stimulated Recall Questionnaire that teachers' translanguaging helped learners to become more engaged and give correct answers. In addition, the results of the data analyzed through descriptive statistics show that translanguaging seemed to have influenced learners' performance in their formative assessment in English and Science lessons. Learners also recorded the highest performance in Filipino despite low cases of translanguaging in that subject, which can be attributed to the fact that Filipino is the learners' lingua franca. Thus, translanguaging may not always be necessary in the Filipino class as learners already understood most of the concepts and terms. The data collected and analyzed here support that teachers' translanguaging promoted learner engagement and concept understanding. The findings in this study are consistent with previous studies (Lasagabaster & Garcia, 2014; Allard, 2014; Cenoz, 2017 Duarte, 2018) which claim that shuttling between languages is a common linguistic behavior among multilingual individuals. A similar behavior was observed among the five Grade 3 multilingual teachers who were observed for two weeks at a time teaching English, Filipino and Science classes. This supports many observations (Hornberger & Lnk, 2012; De Los Reyes, 2018; Makalela 2019) that multilingual teachers naturally shift from one language to another as a way to help learners engage more actively in class and understand their lessons better. The results of this study reveal the following: first, translanguaging can be an effective tool that MTB-MLE teachers should adopt to help facilitate learning. Based on the results of the study, translanguaging is primary used to promote learner engagement and concept understanding. Next, translanguaging demands careful planning. As proposed in this study, using translanguaging as a pedagogical tool requires deliberate steps to ensure that both teachers and learners benefits from it. Third, translanguaging is a deliberate process in that teachers only oscillate between being less deliberate and more deliberate. This was evident when the teachers were observed to be consciously making decisions to shift from a less familiar language to a more familiar one to facilitate learning. Fourth, MTB-MLE teachers need training on the use of translanguaging as a pedagogical tool. This is because teachers need to be familiar with the various translanguaging techniques and functions as identified in this study. Finally, it can be concluded from the results of the study that training in using translanguaging as a pedagogical tool is most needed by teachers whose language of instruction in their subject are is not the most familiar to the learners. Based on the results of this study, I developed a proposed theoretical framework and a set of guidelines for the use of translanguaging as a pedagogical tool.